2018
DOI: 10.20396/parc.v9i4.8651048
|View full text |Cite
|
Sign up to set email alerts
|

Influência da envoltória no desempenho termoenergético de edificações institucionais no semiárido

Abstract: ResumoA eficiência energética em edificações está relacionada à arquitetura bioclimática, que é a adequação da edificação ao clima local. Este estudo objetivou analisar a influência de determinadas características arquitetônicas e construtivas no consumo de eletricidade de edificações situadas em Mossoró, RN, cujo clima é tropical semiárido. Foram coletados dados relativos às características térmicas e geométricas dos elementos arquitetônicos, como: formato da edificação, disposição e uso dos ambientes, orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Monteiro 55 combined DesignBuilder simulation results with computational fluid dynamics (CFD) to enhance the thermal performance of a Brazilian social housing unit located in Macaíba, Rio Grande do Norte. Oliveira and Lunardi 56 used EnergyPlus to assess the influence of architectural design variables on energy consumption of university building located in Mossoró, Rio Grande do Norte. The study indicated the window frames as important feature in the building’s performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Monteiro 55 combined DesignBuilder simulation results with computational fluid dynamics (CFD) to enhance the thermal performance of a Brazilian social housing unit located in Macaíba, Rio Grande do Norte. Oliveira and Lunardi 56 used EnergyPlus to assess the influence of architectural design variables on energy consumption of university building located in Mossoró, Rio Grande do Norte. The study indicated the window frames as important feature in the building’s performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As diretrizes para a obtenção de conforto térmico nesse clima envolvem a utilização de soluções como a proteção contra a radiação solar direta e o aproveitamento adequado da ventilação natural [3] [4]. A performance da ventilação natural resulta do desenho apropriado das aberturas do edifício, que devem considerar a influência das condições do local e seu microclima [5].…”
Section: Fonte: Google Street Viewunclassified